Hygrothermal Performance of Cool Roofs Subjected to Saudi Climates - Saber, Hamed H.; Maref, Wahid; Hajiah, Ali E. (Frontiers in Energy Research, 2019)
In regions with hot climatic conditions such as that in Saudi Arabia, a substantial share of energy is used for cooling the buildings. Many studies have shown that cool (white) roofs can help reduce the cooling energy load and thus the demand for energy over time. Also, cool roofs help reduce the urban heat island during the summer time. This research study focused on determining: (a) whether cool roofs lead to risk of condensation and mold growth in Saudi climates, (b) the amount of energy savings as result of using cool roofs instead of black roofs of same insulation amount, and (c) the reduction in the amount of insulation in cool roof having the same energy performance level as the black roof. As such, numerical simulations were conducted for a roofing system that is commonly used in low-rise buildings in Saudi Arabia in order to asses and compare the energy and hygrothermal performance of cool and black roofs. The roof was subjected to weather conditions of the Eastern Province of Saudi Arabia. The indoor conditions were taken based simple method of ASHRAE Standard 160. The results showed no moisture accumulation occurred from year-to-year after 6 years and 7 years for the black roof and cool roof, respectively, and the highest relative humidities in the black and cool roofs were well below 80% resulting in no risk of condensation and mold growth occurred in these roofs. The main outcome of this study has shown the capabilities of using reflective materials with different short-wave solar absorption coefficients for enhancing the energy performance of roofs and/or reducing the amount of insulation that resulted in same energy performance as black roofs. This study can be used in future for upgrading the Saudi Building Code so as to allow less roof insulation if cool roof is installed.